Unilateral double maxillary paramolars in a non-syndromic child – a rare case report - Acharya, Sonu; Singh, Bismay; Sahoo, Alkananda; Godhi, Brinda Suhas (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Extra teeth are the teeth which are more than the normal number of teeth in jaws. They can be present on a single side or both sides, singular or many, maxillary or mandibular. Paramolars are uncommon supernumerary molars which can be present on buccal or palatal side of molars. Very few reports of supernumerary teeth in maxilla or mandible being paramolars has been stated. No literature on unilateral twin paramolars in maxilla has been reported in literature yet. This is a first case report of unilateral twin paramolars in maxilla in a child. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. This case report describes the presence of unilateral double maxillary paramolars and their handling in a thirteen-year-old boy, whose primary concern was that of severe pain in maxilla on both sides. After an identification of double maxillary paramolars was put forward and established by cone beam computer tomography, both the paramolars were extracted. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Supernumerary teeth have to be removed as soon as detected otherwise they can lead to malocclusion and pain due to caries after pulp involvement.